Pitfalls In Estimating ß-Convergence By Means Of Panel Data: An Empirical Test - Carluccio Bianchi; Federica Calidoni; Mario Menegatti (Università degli Studi di Pavia, Dipartimento di Economia Politica e Metodi Quantitativi (EPMQ), 2009)
This paper aims to test the conjecture advanced in a recent work by Bianchi and Menegatti (2007) that usual !convergence panel regressions may produce biased evidence, due to their inability to distinguish between actual catching-up across countries and decreasing growth rates over time within countries. The test considers different sub-groups in a dataset of 72 countries for the period 1970-2000 and introduces both human capital and proxies for technological differences into the analysis. The results confirm the conjecture that traditional evidence about - convergence may be misleading; they also show that catching-up across countries is weaker than usually claimed and that this process occurred only in some sub-groups of countries.
Keywords: C2; O11; O5; 330; Catching-up; Convergence; Economic Growth; Panel Estimation Techniques